Stereotypes and Interaction of Multliculturalism between Traders in Pasar Proyek Bekasi - Alfiana, Nida; Wildani, Haziqoh Tiara (Universitas Airlangga, 2024)
This research observes the forms of stereotypes and interactions of multiculturalism between traders in Pasar Proyek, Bekasi. This research focuses on the stereotypes that occur between traders from different ethnic which purpose is to find out what stereotypes traders have towards each other. This study uses a qualitative approach that is descriptive using the theory of multiculturalism and stereotypes. To get accurate data and informants, techniques of data collection used in this study were observation, interviews, and documentation. The results of the study show that the stereotypes held by traders in the Pasar Proyek, Bekasi are dominated by positive stereotypes. Besides that, the study also discovered that these traders had a tendency to see auto-stereotypes of their own ethnicity favorably. Additionally, they have strategies for overcoming their racial and cultural divides.